Peningkatkan Hasil Belajar Melalui Model Problem Based Learning Dengan Materi Doa Bapa Kami Di Kelas 1 SD Negeri 11 Semoncol - Dubam Dubam (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to improve the learning outcomes of first-grade students at SD Negeri 11 Semoncol through the implementation of Problem-Based Learning (PBL). The research method used is Classroom Action Research (CAR) conducted in two cycles, implemented offline. The subjects of the study were 10 first-grade students, consisting of 4 males and 6 females, all of whom were Catholic. The study was conducted in the second semester of the 2023/2024 academic year. The results showed that in Cycle I, the classical absorption rate was 71.18% and the learning completeness rate was 70.59%. In Cycle II, there was a significant improvement, with the classical absorption rate reaching 85.88% and the learning completeness rate reaching 100%. Based on these results, it can be concluded that the implementation of the PBL method effectively improved the quality of learning and student learning outcomes. The application of the PBL method successfully enhanced learning outcomes in first-grade students at SD Negeri 11 Semoncol.